AN EMPIRICAL STUDY OF CUSTOMER SATISFACTION TOWARDS E-BANKING SERVICES IN DELHI - Parveen, Sana; Saghir, Vardah; Beg, Sana (Indian Journal of Finance and Banking, 2023)
Digital solutions are a must for Gen Next banking. There has been a surge in tech-enabled digital payments marking a shift in the operations of banks vis-a-vis technology and customer behavioural patterns. The last two years have witnessed a significant rise in digital transactions from 40 billion in 2020 to 87 billion in 2021 in India. Given the increasing preference for contactless banking, banks need to understand their customers better. The purpose of the study is to gauge customer perception towards e-banking services. The study uses the following variables, namely, user interface, content, communication, responsiveness, customer support services, data protection and recommendation of banks to others to find out the relationship with the age of the customers. The questionnaire method is used for conducting the study with a sample size of 200 customers. The cross-tabulation statistical test is applied using SPSS software for data analysis. The study covers the post-pandemic period and chalks out the strategies to increase digitalization in the banking industry which is required for the sector to flourish. Key findings indicate that the banking industry’s current framework needs to find secure solutions to reduce online crimes and e-banking fraud. Based on the findings, better instruments and mechanisms for e-banking services must be put in place. It is recommended to develop a customized user interface for e-banking applications, enforce cyber laws and regulations to curb e-banking frauds and assist customers by setting up in-house cyber redressal cells. Based on time constraints, the study is limited only to 200 customers and the findings rest on the opinion and perception of our chosen sample size. JEL Classification Codes: G21, G28.